Sport as a Tool for Comprehensive Education of Youth - Kosse Rulen Bekirovich (International Journal on Integrated Education, 2022)
In a word, sport means to argue, to compete. A set of movements, consisting of special physical exercises, is at the heart of the concept of sport. At the same time, the social nature of sport, its role in educating a person as a person can hardly be overestimated. The development of society directly led to the development as a concept of physical culture. Sport, which is an integral part of physical culture, still demonstrates its high social significance to this day.